NGTS-2b: an inflated hot-Jupiter transiting a bright F-dwarf. Issue 4 (20th September 2018) - Raynard, Liam; Goad, Michael R; Gillen, Edward; Nielsen, Louise D; Watson, Christopher A; Thompson, Andrew P G; McCormac, James; Bayliss, Daniel; Soto, Maritza; Csizmadia, Szilard; Chaushev, Alexander; Burleigh, Matthew R; et al.
Abstract: We report the discovery of NGTS-2b, an inflated hot-Jupiter transiting a bright F5V star (2MASS J14202949 − 3112074; T eff = 6478^+94_-89 K), discovered as part of the Next Generation Transit Survey ( NGTS ). The planet is in a P = 4.51 d orbit with mass 0.74^+0.13_-0.12 M J, radius 1.595^+0.047_-0.045 R J, and density 0.226^+0.040_-0.038 g cm −3 ; therefore one of the lowest density exoplanets currently known. With a relatively deep 1.0 per cent transit around a bright V = 10.96 host star, NGTS-2b is a prime target for probing giant planet composition via atmospheric transmission spectroscopy. The rapid rotation (v sin i = 15.2 ± 0.8 km s −1 ) also makes this system an excellent candidate for Rossiter–McLaughlin follow-up observations, to measure the sky-projected stellar obliquity. NGTS-2b was confirmed without the need for follow-up photometry, due to the high precision of the NGTS photometry.